Analisis Pengaruh Harga, Promosi, Dan Kualitas Produk Terhadap Keputusan Pembelian Pasca Pandemi Analysis of the Effect of Price, Promotion, and Product Quality on Purchase Decisions - Clara Shinta Anggraeni; Elvi Ekawati; Khorifah Arum (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
MSMEs or Micro, Small and Medium Enterprises are the mainstays of the community's economic sector. The digital revolution, making many changes to MSMEs where there is a change in consumer shopping styles from offline to online. Therefore, prospective UMKM or MSME scale entrepreneurs need to have sufficient insight. This study aims to analyze the effect of price, promotion, and product quality on purchasing decisions during a pandemic. This research method focuses on quantitative research through descriptive and inferential statistics. The data collection method used in this study was to use a questionnaire technique or a questionnaire by distributing several written statements to consumers who happened to be found at Various Snacks Clara Cooking Chips, Yogyakarta. The number of respondents who will be sampled is 120 people. The conclusion that can be drawn from the research results is that price and product quality have a significant effect on purchasing decisions, while promotions have no significant effect on purchasing decisions. Suggestions for further research are that it is necessary to carry out further research with a more varied number of variables, also increasing the number of respondents and not just in one place to get very accurate results.